Soil structure changes evaluated with computed tomography - Pires, Luiz Fernando; Santos Bacchi, Osny Oliveira (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate in millimetric scale changes in soil bulk density and porosity, using the gamma-ray computed tomography in soil samples with disturbed structure due to wetting and drying (W-D) cycles. Soil samples with 98.1 cm3 were sieved using a 2 mm mesh and homogenously packed in PVC cylinders. Soil samples were submitted to 1, 2, and 3 W-D cycles. Control samples were not submitted to W-D cycles. After repetitions of W-D cycles, soil sample porosity decreased and soil layers became denser. Computed tomography allowed a continuous analysis of soil bulk density and also soil porosity along millimetric (0.08 cm) layers, what cannot be provided by traditional methods used in soil physics.